2000
DOI: 10.1046/j.1365-2133.2000.03851.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucoderma associated with flares of erythrodermic cutaneous T-cell lymphomas: four cases

Abstract: We describe four patients with erythrodermic cutaneous T-cell lymphomas (two with erythrodermic mycosis fungoides, and two with Sézary syndrome) who presented with extensive hypopigmented lesions that occurred during flares of their cutaneous disease. These cases must be distinguished from previously described hypopigmented mycosis fungoides where hypopigmented lesions were the sole manifestation of the lymphoma. In two cases a biopsy was performed on hypopigmented skin, showing an infiltrate of atypical lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 16 publications
0
35
1
Order By: Relevance
“…1 In this context, hypopigmentation during flares of erythrodermic cutaneous T-cell lymphoma has been purported to result from reaction of cytotoxic T-cells. 12 On ultrastructural examination, damaged melanosomes 10 and a decreased number of melanosomes 11 have been observed in the lesional skin. The pathogenesis of hypopigmentation in vitiligo is also not completely understood; suggested mechanisms include autoimmune, neural, biochemical, oxidative stress, autocytotoxic, viral, and melanocyte detachment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In this context, hypopigmentation during flares of erythrodermic cutaneous T-cell lymphoma has been purported to result from reaction of cytotoxic T-cells. 12 On ultrastructural examination, damaged melanosomes 10 and a decreased number of melanosomes 11 have been observed in the lesional skin. The pathogenesis of hypopigmentation in vitiligo is also not completely understood; suggested mechanisms include autoimmune, neural, biochemical, oxidative stress, autocytotoxic, viral, and melanocyte detachment.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] The mechanism of hypomelanosis in hypopigmented mycosis fungoides is as yet unclear. Damaged melanosomes 10 and a decreased number of melanocytes 11,12 have been reported in hypopigmented mycosis fungoides lesions.…”
mentioning
confidence: 99%
“…This may be similar to melanoma-associated depigmentation that develops in melanoma, which is thought to result from a CD8+ cytotoxic reaction against melanoma tumor cells [25]. Other studies have associated therapeutic agents, including treatment with PUVA and IFNα, with vitiligo in CTCL patients [9,10,11,22,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…They suggested that a dense dermal lymphocytic infiltrate composed mainly of helper T cells contributed to melanocyte destruction by stimulating a cell-mediated cytotoxic process. More than a decade later, Bouloc et al [9] described four erythrodermic CTCL patients who developed vitiligo during disease flares. It was hypothesized that depigmentation resulted from the cytotoxic activity of reactive tumor cells directed against melanocyte antigens or from autoantibodies such as antityrosinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation